Quality of Service of the Mobile Storytelling Program for Children and Teenagers (DARLING) by the East Java Provincial Library and Archives Office as a Library Service Innovation in Surabaya - Firiznanda, Muhammad Fa'iq; Mubarak, Yusya Hammam; Fauzi, Ahmad; Salsabila, Naila; Perdana, Rizky Nurhidayat (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This study is based on a phenomenon, namely the fairly good statistical results of public satisfaction with the Children's and Teenagers' Fairy Tales (Darling) program amidst various obstacles faced. This study aims to further identify the actual quality of service produced by the East Java Provincial Library and Archives Service in the Darling program so as to obtain good satisfaction from the community. This study uses a qualitative descriptive method, namely describing the results of the analysis using the Parasuraman, Zeithaml, and Berry service quality theory based on the reality that occurs based on data collected through interviews, observations, and documentation as well as supporting data such as books, journals, or website articles. This study shows results where the five aspects used to measure the quality of the Darling program service are met well, so that it provides an understanding of what efforts are made by the East Java Provincial Library and Archives Service so that this program can produce maximum service and make the level of public satisfaction optimal. Keywords: Darling, Quality, Service, Mobile Library, Program